Histological Chorioamnionitis: Effects on Premature Delivery and Neonatal Prognosis - Gulin Erdemir; Nilgun Kultursay; Sebnem Calkavur; Osman Zekioğlu; Ozge Altun Koroglu; Bilin Cakmak; Mehmet Yalaz; Mete Akisu; Sermet Sagol (Pediatrics and Neonatology)
Chorioamnionitis is closely related to premature birth and has negative effects on neonatal morbidity and mortality. Methods: In this prospective study, 43 mothers who delivered earlier than 35 gestational weeks and their 57 infants were evaluated clinically and with laboratory findings. Placentas and umbilical cords were investigated histopathologically for chorioamnionitis and funisitis. Results: The overall frequency of clinical and histological chorioamnionitis (HCA) was 8.3% and 23.2%, respectively. The frequency of HCA was 47.3% and 83.3% in mothers delivered <32 weeks and <30 weeks, respectively. Maternal demographic and clinical findings and also leukocyte and C-reactive protein values were not indicative of HCA. Infants of mothers with HCA had significantly lower Apgar scores together with higher SNAP-PE-II and CRIB scores. These infants had increased mechanical ventilator and surfactant requirements, higher incidences of patent ductus arteriosus, early sepsis, and bronchopulmonary dysplasia, and higher mortality rates. The effect of HCA on neonatal morbidity and mortality was more prominent than the effect of low birthweight and lower gestational age. Conclusion: Chorioamnionitis not only causes premature deliveries, but is also associated with neonatal complications and increased mortality. Clinical findings and infectious markers in mother or infant do not predict the diagnosis of histological chorioamnionitis. Therefore, placental histopathology may have a role in predicting neonatal outcome in premature deliveries, especially those below 30 weeks.